The Legend of Sargon: A Study of the Akkadian Text and the Tale of the Hero Who Was Exposed at Birth - Brian, Lewis
Diss.; K.7249 (unedited) also used for col. ii; Cf. Diss. Abstr. 38 (1977-78) 755-A.